A meta‐analysis of deep brain structural shape and asymmetry abnormalities in 2, 833 individuals with schizophrenia compared with 3, 929 healthy volunteers via the ENIGMA Consortium. Issue 1 (8th September 2021) - Gutman, Boris A.; van Erp, Theo G.M.; Alpert, Kathryn; Ching, Christopher R. K.; Isaev, Dmitry; Ragothaman, Anjani; Jahanshad, Neda; Saremi, Arvin; Zavaliangos‐Petropulu, Artemis; Glahn, David C.; Shen, Li; Cong, Shan; et al.
Abstract: Schizophrenia is associated with widespread alterations in subcortical brain structure. While analytic methods have enabled more detailed morphometric characterization, findings are often equivocal. In this meta‐analysis, we employed the harmonized ENIGMA shape analysis protocols to collaboratively investigate subcortical brain structure shape differences between individuals with schizophrenia and healthy control participants. The study analyzed data from 2, 833 individuals with schizophrenia and 3, 929 healthy control participants contributed by 21 worldwide research groups participating in the ENIGMA Schizophrenia Working Group. Harmonized shape analysis protocols were applied to each site's data independently for bilateral hippocampus, amygdala, caudate, accumbens, putamen, pallidum, and thalamus obtained from T1‐weighted structural MRI scans. Mass univariate meta‐analyses revealed more‐concave‐than‐convex shape differences in the hippocampus, amygdala, accumbens, and thalamus in individuals with schizophrenia compared with control participants, more‐convex‐than‐concave shape differences in the putamen and pallidum, and both concave and convex shape differences in the caudate. Patterns of exaggerated asymmetry were observed across the hippocampus, amygdala, and thalamus in individuals with schizophrenia compared to control participants, while diminished asymmetry encompassed ventral striatum and ventral and dorsal thalamus. Our analyses also revealed that higher chlorpromazine dose equivalents and increased positive symptom levels were associated with patterns of contiguous convex shape differences across multiple subcortical structures. Findings from our shape meta‐analysis suggest that common neurobiological mechanisms may contribute to gray matter reduction across multiple subcortical regions, thus enhancing our understanding of the nature of network disorganization in schizophrenia. Abstract : Our manuscript reports the first, large prospective subcortical shape meta‐analysis to date, comparing individuals with schizophrenia and healthy controls. Twenty‐one institutions worldwide contributed 24 cross‐sectional study samples to this study via the Enhancing Neuro Imaging Genetics Through Meta‐Analysis (ENIGMA) Consortium, Schizophrenia Working Group, totaling 2, 833 individuals with schizophrenia and 3, 929 healthy controls. The study utilized a prospective meta‐analysis approach with state‐of‐the‐art harmonized shape analysis protocols. We report robust patterns of subcortical shape and asymmetry differences, and associations with medication and symptoms that spanned multiple neighboring subcortical structures, which have not been previously reported in individual studies with consistency.